2020
DOI: 10.1101/2020.09.13.295568
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sustained neural activity correlates with rapid perceptual learning of auditory patterns

Abstract: Recurring structures forming regular patterns are common in sounds. Learning such patterns is thought to be crucial for accurate auditory perceptual organization (scene analysis) and efficient recognition and prediction of sounds. The current study investigated the behavioral and neural signatures of rapid perceptual learning of regular patterns in sounds. In six behavioral and EEG experiments with over 120 human participants from both sexes, we show that individuals are faster to detect regular patterns, are … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 65 publications
(152 reference statements)
1
3
0
Order By: Relevance
“…For both younger and older adults, we observed that sustained neural activity increased after the onset of a sound pattern relative to sounds without a pattern. Previous work in younger adults has revealed similar increases in sustained activity for different types of patterns, including tone sequences such as those we have utilized here (Gutschalk et al, 2002; Ross et al, 2002; Keceli et al, 2012; Barascud et al, 2016; Sohoglu and Chait, 2016; Teki et al, 2016; Southwell et al, 2017; Herrmann and Johnsrude, 2018b; Southwell and Chait, 2018; Herrmann et al, 2019; Herrmann et al, 2021).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…For both younger and older adults, we observed that sustained neural activity increased after the onset of a sound pattern relative to sounds without a pattern. Previous work in younger adults has revealed similar increases in sustained activity for different types of patterns, including tone sequences such as those we have utilized here (Gutschalk et al, 2002; Ross et al, 2002; Keceli et al, 2012; Barascud et al, 2016; Sohoglu and Chait, 2016; Teki et al, 2016; Southwell et al, 2017; Herrmann and Johnsrude, 2018b; Southwell and Chait, 2018; Herrmann et al, 2019; Herrmann et al, 2021).…”
Section: Discussionsupporting
confidence: 62%
“…It is clear from previous work that temporally regular – and thus predictable – structure in sounds that forms a pattern elicits sustained neural activity (Gutschalk et al, 2002; Barascud et al, 2016; Herrmann and Johnsrude, 2018b). However, additional work suggests that the magnitude of pattern-related sustained activity is related to the degree of novelty or predictability of a pattern, such that sustained activity decreases when a pattern is frequently, compared to infrequently, heard (Gutschalk et al, 2007; Herrmann et al, 2021). A reduction in sustained activity in older adults may thus result from reduced processing of the pattern as well as from reduced novelty of the pattern, but further behavioral research is needed to investigate the perceptual consequences of the altered cortical sensitivity observed here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations